THE ILLICIT DRUG TRADE IN THE COLLAO PLATEAU – PUNO, FROM CRITICAL CRIMINOLOGY - Wilmer Mamani Mamani (2020)
The present work, reveals the investigation from the critical criminological perspective, a brief investigation that had as objectives: to integrate the main postulates of the criminologists critical to the investigation of the crime of Illicit Drug Trafficking, to present critical positions to the criminal system, to capitalist system, determine the route of the drug in Puno and its main exits; by means of the sociological and dogmatic method, the connection of the postulates on the study of the criminal or deviant of Richard Quinney, Taylor, Walton, Young, Alessandro Baratta among other critical criminologists is established, to study who incurs the crime of Illicit Traffic in Drugs, confirming that many postulates serve to have a real vision of crime and the offender; In addition to this, in order not to lose the style of Critical Criminology, we find the crime of Illicit Drug Trafficking as an instrument of international control, which since the existence of international treaties, dedicate their efforts to make international crimes more severe among them the Illicit Drug Trafficking. In that knowledge we are dedicated to studying our reality in Puno, bearing in mind the socio-economic reality, to determine who commits the crime, what is and was its condition of the Puneño that integrates those organizations dedicated to the Illicit Drug Trafficking. For this, we determine the route of the drug, through interviews and journalistic notes, which allows us to know how the socioeconomic conditions of the people who live within the route or live next to it are, to question the performance of the criminal system and its operators when fighting this crime.